Twilight [videorecording (Blu-Ray + DVD)] - Hardwicke, Catherine; Pattinson, Robert, 1986-; Stewart, Kristen, 1990-; Lautner, Taylor, 1992-; Burke, Billy; Facinelli, Peter, 1973-; Meyer, Stephenie, 1973- (Twilight series blu-ray, 2018)
When Bella Swan moves to gloomy Forks, Washington to live with her father and begins her junior year in high school, she meets and falls in love with Edward Cullen who is secretly a vampire.